Body Mass Index and waist circumference as predictors of cardiovascular risk in diabetic patients (Research, Society and Development, 2021)
Obesity is a highly prevalent condition in diabetics. The aim was to observe two methods of obesity evaluation: BMI and abdominal circumference (AC) and its association with cardiovascular risk factors in diabetics. Through a prospective, cross-sectional study, diabetics seen in primary care were assessed. Body weight and height were measured to calculate BMI; AC and hip circumference for waist / hip ratio. Biochemistry, well as demographic data were collected from records for clinical analysis. Blood pressure measured at the evaluation. Using BioStat 5.0 for statistical. Prevalence of overweight and obesity were high as the prevalence of cardiovascular risk factors, included AC. Prevalence of Metabolic Syndrome (MS) was 67.1%. There was no association between the risk factors and anthropometry. AC was able to predict SM. It is recommended to use the AC in clinical practice, but not as unique clinical parameter, since the possibility of misdiagnosis and treatment delay.